Intricacies of overhead cost allocations and distortion in costing: a synthesis of the literature / Bülend Terzioglu - Terzioglu, Bülend (Accounting Research Institute (ARI), 2012)
In the early 1920s, direct labour comprised most of the total cost of manufacturing, and allocating overheads using direct labour hours or direct labour cost was sufficient for inventory valuation purposes, which was then the primary object of cost accounting. However, the upsurge of manufacturing overhead as a percentage of manufacturing cost at the expense of direct labour and proliferation of product lines complicated the otherwise relatively straightforward process of overhead cost allocation. Empirical evidence demonstrates that our understanding of how best to allocate overheads is at a nascent stage, and surprisingly most managers still do not know their costs. Moreover, managers have grave concerns about the current practice that allocates overheads to products in an arbitrary fashion. These concerns stem from the fact that managerial decisions are based on cost information furnished by management accountants, which is ostensibly inaccurate. This conceptual discussion paper integrates the extant accounting literature on overhead cost allocation, discusses the ramifications of inaccurate cost allocation, and highlights areas for further research. Consistent with many earlier studies, the findings reported in this article show that the primacy of arbitrary cost allocations is maintained, and that managers are unsure of the accuracy of their costs and apprehensive about the problems emanating from inaccurate cost allocations.